2015
DOI: 10.1155/2015/490295
|View full text |Cite
|
Sign up to set email alerts
|

TRAF1/C5but NotPTPRCVariants Are Potential Predictors of Rheumatoid Arthritis Response to Anti-Tumor Necrosis Factor Therapy

Abstract: Background. The aim of our work was to replicate, in a Southern European population, the association reported in Northern populations between PTPRC locus and response to anti-tumor necrosis factor (anti-TNF) treatment in rheumatoid arthritis (RA). We also looked at associations between five RA risk alleles and treatment response. Methods. We evaluated associations between anti-TNF treatment responses assessed by DAS28 change and by EULAR response at six months in 383 Portuguese patients. Univariate and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…In previous studies of rheumatoid arthritis, high LD values were found between the TRAF1 and C5 genes, a result that precluded the determination of which of these two genes is responsible for the exacerbated inflammatory response (43). However, an LD of Ͻ78 between both genes was found in our study, a value like that reported by Kurreeman et al for these genes (16).…”
Section: Fig 4 Association Of C5 Constructed Haplotypes With Epilepsysupporting
confidence: 52%
“…In previous studies of rheumatoid arthritis, high LD values were found between the TRAF1 and C5 genes, a result that precluded the determination of which of these two genes is responsible for the exacerbated inflammatory response (43). However, an LD of Ͻ78 between both genes was found in our study, a value like that reported by Kurreeman et al for these genes (16).…”
Section: Fig 4 Association Of C5 Constructed Haplotypes With Epilepsysupporting
confidence: 52%
“…In total, 47 studies were included in the analysis; 42 candidate gene studies 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 and 5 genome-wide association studies (GWAS) 60 , 61 , 62 , 63 , 64 analysing responders versus non-responders from anti-TNF therapy in RA ( Table 1 ). Two studies reported associations between polymorphisms and treatment response in juvenile idiopathic arthritis (JIA) 37 , 50 and the others on adult RA.…”
Section: Resultsmentioning
confidence: 99%
“…Increased serum levels of TRAF1 correlate with disease activity and autoantibodies in RA patients. Moreover, SNPs in the TRAF1-C5 locus may predict the clinical response to anti-TNF therapy (79, 80). The expression of TRAF1 is also significantly higher in inflamed and non-inflamed tissues of patients with inflammatory bowel disease compared to those in control patients (81).…”
Section: Autoimmunity Rheumatoid-arthritis Associated Sepsis and Camentioning
confidence: 99%